Impact of Dietary Fiber Enrichment on the Sensory Characteristics and Acceptance of French Baguettes. Issue 5 (12th September 2013) - Martin, Christophe; Chiron, Hubert; Issanchou, Sylvie
<x xml:space="preserve">Abstract</x> Abstract The purpose of this study was to evaluate the consequences of dietary fiber (DF) enrichment in standard or superior quality French baguettes. Sensory characteristics of five experimental breads and seven commercial breads were described by a trained panel using a conventional sensory profile. The same set of breads was also evaluated by a panel of consumers who had to rate their expected liking based on the external appearance of a whole bread and then their perceived liking based on the tasting of a sample of that bread. DF enrichment was responsible for deterioration in the expected and perceived liking of breads. However, this deterioration was less substantial when the DF enrichment was realized in superior quality breads, such as baguettes obtained using a traditional French bread‐making process. Indeed, this combination produces baguettes that are well appreciated by consumers upon tasting despite the unconventional sensory characteristics of these baguettes. Practical Applications As demonstrated in the present study, even when enriched in dietary fibers, baguettes produced according to traditional French bread‐making process are well appreciated by consumers. In France, the French baguette is frequently consumed by a large proportion of the population. Thus, this product could be a good medium for increasing dietary fiber intake. Applied to a large scale, this nutritional improvement of French baguette could contribute to satisfy the national and international nutritional recommendations, which encourage the increase of complex carbohydrates in the diet.